2019
DOI: 10.1093/molehr/gaz042
|View full text |Cite
|
Sign up to set email alerts
|

In ovaries with high or low variation in follicle size, granulosa cells of antral follicles exhibit distinct size-related processes

Abstract: Antral follicle size might be a valuable additive predictive marker for IVF outcome. To better understand consequences of antral follicle size as a marker for reproductive outcome, we aimed to obtain insight in follicle size-related granulosa cell processes, as granulosa cells play an essential role in follicular development via the production of growth factors, steroids and metabolic intermediates. Using the pig as a model, we compared gene expression in granulosa cells of smaller and larger follicles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
7
2
Order By: Relevance
“…Smaller follicles were more proliferative, as shown by a higher expression of genes involved in cell cycle progression and protein translation, while larger follicles were more differentiated as shown by a higher expression of follicular maturation markers. Different from Costermans et al, 2019a; in the current analysis follicle size was similar in high versus low weight loss sows, and observed effects are therefore due to lactational weight loss. These results indicate that besides described effects of lactational weight loss on follicle size, weight loss also sustains granulosa cell proliferation which may delay granulosa cell differentiation, independent of follicle size.…”
Section: Introductioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Smaller follicles were more proliferative, as shown by a higher expression of genes involved in cell cycle progression and protein translation, while larger follicles were more differentiated as shown by a higher expression of follicular maturation markers. Different from Costermans et al, 2019a; in the current analysis follicle size was similar in high versus low weight loss sows, and observed effects are therefore due to lactational weight loss. These results indicate that besides described effects of lactational weight loss on follicle size, weight loss also sustains granulosa cell proliferation which may delay granulosa cell differentiation, independent of follicle size.…”
Section: Introductioncontrasting
confidence: 94%
“…Together, this may suggest that granulosa cells of sows with a high versus low weight loss during lactation are more proliferative. To assess this, protein expression of Ki‐67, a proliferation marker (Gerdes et al, 1984), was compared for granulosa cells of sows with high versus low weight loss during lactation (see Costermans et al, 2019a for experimental details). Ki‐67 protein expression tended to be higher ( p = 0.09) for sows with a high versus low weight loss during lactation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative transcript abundance of INHBA was lower in CCs derived from SF than those from MF, whereas the transcript abundance of FSHR, FST, LHR and NR2F6 was higher in CCs derived from SF. A previous study that analysed the transcriptomic profile of granulosa mural cells derived from SF and MF found no significant effect of follicle diameter for some of the genes analysed (LHR, FST, FSHR, INHBA and VEGFA) in the present study (Costermans et al., 2019).…”
Section: Discussioncontrasting
confidence: 59%
“…Insulin-like growth factor 1 (IGF1) and FSH signals are two important growth factors for folliculogenesis and increase with follicle maturation ( 9 , 10 ). Studies in pigs have shown that direct exposure to high concentrations of glucocorticoids decreases ovarian IGF1 production both in vitro ( 11 ) and in vivo ( 12 ).…”
Section: Introductionmentioning
confidence: 99%